Nudging, Fast and Slow: Experimental Evidence from Food Choices Under Time Pressure - Paul M. Lohmann; Elisabeth Gsottbauer; Christina Gravert; Lucia A. Reisch (CESifo GmbH, 2025)
Understanding when and why nudges work is crucial for designing interventions that consistently and reliably change behaviour. This paper explores the relationship between decision-making speed and the effectiveness of two nudges – carbon footprint labelling and menu repositioning – aimed at encouraging climate-friendly food choices. Using an incentivized online randomized controlled trial with a quasi-representative sample of British consumers (N=3,052) ordering meals through an experimental food-delivery platform, we introduced a time-pressure mechanism to capture both fast and slow decision-making processes. Our findings suggest that menu repositioning is an effective tool for promoting climate-friendly choices when decisions are made quickly, though the effect fades when subjects have time to revise their choices. Carbon labels, in contrast, showed minimal impact overall but reduced emissions among highly educated and climate-conscious individuals when they made fast decisions. The results imply that choice architects should apply both interventions in contexts where consumers make fast decisions, such as digital platforms, canteens, or fast-food restaurants to help mitigate climate externalities. More broadly, our findings suggest that the available decision time in different contexts might at least partly explain differences in effect sizes found in previous studies of these nudges.
Keywords: C90; D04; I18; D90; Q18; Q50; 330; carbon-footprint labelling; choice architecture; food-delivery apps; low-carbon diets; dual-process models; system 1